The LET connection : towards a successful review - Hilbero, Lydia L.; Delos Santos, Helen F.; Villena, Danilo K.; Manzano, Sonia R.; Rosemarievic Villena-Diaz, Rose ; Aguirre, Roderick M.; Villanueva, Francis Jasson Z. (Mandaluyong City Books Atbp. Publishing Corp., 2006)
This reviewer entitled The LET Connection: Towards a Successful Review was conceived to help the teacher education graduates pass the Licensuyre Examination for Teachers (LET), as well as teachers who want to keep abreast with the current practices in education. It will also serve as a reference book for education students
Keywords: Teachers- examinations